Application of metallic nanoparticle-biochars with ionic liquids for thermal transfer fluids. (July 2020) - Huang, Hsin-Liang; Huang, Zi-Hao; Chu, Yi-Cheng; Lin, Hong-Ping; Chang, Yun-Jung
Abstract: Ionic liquids (ILs (1-butyl-3-methylimidazolium chloride ([C4 mim][Cl]) and 1-butyl-3-methylimidazolium tetrafluoroborate ([C4 mim][BF4 ]))) were used as heat transfer fluids for solar thermal collectors. The additive of ILs was biochar containing copper and silver nanoparticles (Cu–Ag/biochar) to improve the adsorption of solar irradiation and thermal conductivities. After impregnation and reduction processes, nanoparticles such as Cu, CuO, Cu(OH)2, Ag, and Ag2 O were found in the biochar by X-ray powder diffraction (XRD) spectroscopy. With adding 2% Cu–Ag/biochar into the ILs, the thermal conductivities of [C4 mim][Cl] and [C4 mim][BF4 ] containing 10% Cu–1% Ag/biochar were individually increased 9.2 and 6.6 times compared to the base ILs due to the high graphitization of biochar and metallic nanoparticles. The 1 H NMR (nuclear magnetic resonance) features of the imidazole ring and methyl group in the ILs were highly disturbed due to the formation of weak or strong hydrogen bonds between the cations in ILs and Cu–Ag/biochar. The high hydrogen bond acceptance of anions in ILs also affected the thermal properties. The thermal properties of the metals/biochar [C4 mim][Cl] were better than those of metals/biochar [C4 mim][BF4 ] due to high hydrogen bond acceptance of [Cl] - . The strong hydrogen bonds between the Cu–Ag/biochar and the cations and anions in ILs result in thermal properties of heat transfer fluids. Under simulated sunlight, the temperatures of [C4 mim][Cl] and [C4 mim][BF4 ] containing 10% Cu–1% Ag/biochar rose from 304 to 345 and 340 K within 24 min, respectively. A novel heat transfer fluid was developed for high adsorption of irradiation, high thermal conductivities, and speedy transfer of heat. Highlights: The thermal conductivities of ILs was increased by graphitization of biochar. Formation of hydrogen bonds in ILs and additives affect thermal properties of ILs. The metals/biochar ILs had good adsorption of irradiation and thermal properties.